A strain energy density based life prediction model for notched components in low cycle fatigue regime. (October 2021) - Zhao, Peng; Lu, Tian-Yang; Gong, Jian-Guo; Xuan, Fu-Zhen; Berto, Filippo
Abstract: Fatigue life prediction of engineering components is essential for safe operation of mechanical systems. Energy based models have attracted much attention due to the combined considerations of stress and strain behavior, especially in low cycle fatigue regime. In this work, a new plastic strain energy density (PSED) based life prediction model for notched components subjected to cyclic loading is proposed, in which cyclic stress-strain responses under stress- and strain-controlled modes are both introduced. Experimental tests on 304 stainless steel smooth and notched plate/bar components are conducted for calibrations and verifications. The prediction capability of the proposed model is verified by experimental results. Highlights: A modified plastic strain energy density (PSED)-based model is proposed. Fatigue properties under both stress and strain cycling are considered. Applicability of the proposed model to low cycle fatigue is verified.